Hubungan Kadar High Density Lipoprotein (HDL) Dengan Kejadian Hipertensi - Muhammad Syahril Rafsanjani; Asriati Asriati; Andi Noor Kholidha; La Ode Alifariki (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2019)
Eventyally this study aims to determine the correlation between HDL levels as a risk factor of hypertension. This research used observational analytic design with cross sectional approach. The independent variable was total cholesterol levels and the dependent variable was hypertension. The research was located in Selabangga Village, Moramo District with the total sample of 57 samples based on the inclusion and exclusion criteria selected by the purposive sampling method. These data were obtained by using a measurement instrument of HDL level (lipids Pro) and blood pressure measurement devices (aneroid sphygmomanometer). The result of data was processed by Chi Square statistic test and Prevalence Odds Ratio (POR). The results of HDL research on hypertension found that from the 57 respondents, 34 respondents (56,9%) were hypertension and 25 respondents (43,9%) were hypertension whit HDL level at risk. Based on Chi-square statistical test, it was found that between HDL level and hypertension showed p value of 0.000 <α (0,05). While, the POR value of the HDL variable was 10,000 CI 95% 2,865-34,899. The conclusion of this study was the HDL level correlated as a risk factor for hypertension incidence.